Short- and long-term effects of imatinib in hospitalised COVID-19 patients : A randomised trial - Halme, Alex L.E.; Laakkonen, Sanna; Rutanen, Jarno; Nevalainen, Olli P.O.; Sinisalo, Marjatta; Horstia, Saana; Mustonen, Jussi M.J.; Pourjamal, Negar; Vanhanen, Aija; Rosberg, Tuomas; Renner, Andreas; Perola, Markus; et al. (Academic Press, 2025)
Objectives
We studied the short- and long-term effects of imatinib in hospitalised COVID-19 patients.
Methods
Participants were randomised to receive standard of care (SoC) or SoC with imatinib. Imatinib dosage was 400mg daily until discharge (max 14 days). Primary outcomes were mortality at 30 days and 1 year. Secondary outcomes included recovery, quality of life and long COVID symptoms at 1 year. We also performed a systematic review and meta-analysis of randomised trials studying imatinib for 30-day mortality in hospitalised COVID-19 patients.
Results
We randomised 156 patients (73 in SoC and 83 in imatinib). Among patients on imatinib, 7.2% had died at 30 days and 13.3% at 1 year and in SoC 4.1% and 8.2% (adjusted HR 1.35, 95% CI 0.47–3.90). At 1-year, self-reported recovery occurred in 79.0% in imatinib and in 88.5% in SoC (RR 0.91, 0.78-1.06). We found no convincing difference in quality of life or symptoms. Fatigue (24%) and sleep issues (20%) frequently bothered patients at one year. In the meta-analysis, imatinib was associated with a mortality risk ratio of 0.73 (0.32–1.63; low certainty evidence).
Conclusions
The evidence raises doubts regarding benefit of imatinib in reducing mortality, improving recovery and preventing long COVID symptoms in hospitalised COVID-19 patients.